Association of first-trimester angiogenic factors with placental histological findings in late-onset preeclampsia. (June 2016) - Triunfo, Stefania; Crovetto, Francesca; Crispi, Fatima; Rodriguez-Sureda, Victor; Dominguez, Carmen; Nadal, Alfons; Peguero, Anna; Gratacos, Eduard; Figueras, Francesc
Abstract: Objective: To explore in women with late-onset preeclampsia (PE) the association between maternal levels of angiogenic/antiangiogenic factors in the first trimester of pregnancy and histological findings attributable to placental underperfusion (PUP). Methods: A nested case-control cohort study was conducted in 73 women with pregnancies complicated by late-onset PE (>34 weeks at delivery) matched with controls. First trimester uterine artery Doppler (UtA); maternal levels of placental growth factor (PlGF) and soluble fms-like tyrosine kinase-1 (sFlt-1) were retrieved. Placentas were histologically evaluated using a hierarchical and standardized classification system. One-way ANOVA with linear polynomial contrast or linear-by-linear association test was performed to test the hypothesis of a linear association across study groups (controls, PE without PUP and PE with PUP). Results: In 54 (74%) placentas, 89 placental histological findings qualifying for PUP were found. Across study groups, significant values were observed in maternal levels of decreased PlGF (MoM values: 1.53, 1.41 and 1.37; p < 0.001), increased sFlt-1 (MoM values: 3.11, 3.11 and 3.22; p = 0.002), increased sFlt-1/PlGF ratio (MoM values: 2.3, 2.3 and 2.44; p < 0.001), abnormal UtA Doppler (MoM values: 1, 1.26 and 1.32; p < 0.001), and worse perinatal outcomes in terms of gestational age at delivery, cesarean section for not reassuring fetal status, birth weight and neonatal acidosis. Discussion: In late-onset PE an imbalance of circulating angiogenic and anti-angiogenic factors already present at 8–10 weeks of pregnancy was associated with histological findings reflecting placental insufficiency. An early first trimester screening by angiogenic factors might help to identify patients with placental involvement among late-onset PE cases. Conclusion: In late-onset preeclampsia, first-trimester uterine Doppler and circulating levels of angiogenic/antiangiogenic factors are associated with placental underperfusion. Highlights: Late-onset preeclampsia is associated with adverse perinatal outcomes. First study to investigate the relationship between first trimester PlGF-sFlt-1 and placental histology. First trimester PlGF and sFlt-1 levels are associated with histological placental insufficiency.